Amplitude mode in the planar triangular antiferromagnet Na0.9MnO2 - Rebecca L. Dally (Nature Portfolio, 2018)
Oscillations of the order parameter amplitude in magnetically ordered materials provide condensed matter analogues of the Higgs boson but in most cases they are unstable. Dally et al. show that the quasi-one-dimensional magnet α-Na0.9MnO2 supports stable amplitude excitations.